Therapeutic Levels of Lopinavir in Late Pregnancy and Abacavir Passage into Breast Milk in the Mma Bana Study, Botswana. Issue 4 (May 2013) - Shapiro, Roger L; Rossi, Steven; Ogwu, Anthony; Moss, Mary; Leidner, Jean; Moffat, Claire; Lockman, Shahin; Moyo, Sikhulile; Makhema, Joseph; Essex, Max; Capparelli, Edmund
Background: Pharmacokinetic data for lopinavir in late pregnancy and in breastfeeding are limited, and no data for abacavir in breast milk are available. Methods: Women in the Mma Bana Study initiated HAART from 18 to 34 weeks of gestation. We determined trough plasma and whole breast milk concentrations of lopinavir (LPV), abacavir (ABC), nevirapine (NVP), lamivudine (3TC) and zidovudine (ZDV) among separate subsets of pregnant and breastfeeding women, and in plasma of exposed infants. Lopinavir was measured 1 month after starting HAART or 1 month postpartum, and other drugs were measured 1 month postpartum. Results: Sampling occurred a median of 14 h (range 11–17) from last maternal drug ingestion. Although 50% higher median LPV levels were seen in postpartum than antepartum plasma (8.29 μg/ml versus 5.51 μg/ml; P =0.02), antepartum levels with standard LPV dosing were therapeutic for all women (>1.0 μg/ml). Very low LPV levels (<0.25 μg/ml) were detected in breast milk. Median ABC levels in breast milk were 85% of those in plasma (0.057 μg/ml versus 0.067 μg/ml). Breast milk concentrations of NVP and 3TC were 27% and 74% of plasma levels, respectively. At these trough maternal time points, only NVP was detectable in potentially inhibitory levels in breastfeeding infants, and most infants had non-detectable levels of LPV, ABC, ZDV and 3TC via maternal breast milk. Conclusions: Standard LPV dosing achieved therapeutic levels in pregnancy and no appreciable concentrations in breast milk. ABC is detectable in breast milk at similar concentrations to plasma, but does not result in appreciable infant exposure.